Who never tells a lie? - Christoph Vanberg (University of Heidelberg, Department of Economics, 2015)
Erat and Gneezy (2012) conduct an experiment to test whether people avoid lying in a situation where doing so would lead to a Pareto improvement. They conclude that many people exhibit such a "pure lie aversion." I argue that the experiment does not provide a reliable test for such an aversion, and that the evidence does not support the authors' conclusion. I conduct two new experiments which are explicitly designed to test for a 'pure' aversion to lying, and find no evidence for the existence of such a motivation. I discuss the implications of the findings for moral behavior and rule following more generally.
urn:nbn:de:bsz:16-heidok-181483
Keywords: 330; Lying; Deception; Morality; Ethics; Experiments; Verhalten; Ethik; Multikriterielle Entscheidungsanalyse; Verhaltensökonomik